Capsaicinoids improve egg production by regulating ovary nuclear transcription factors against heat stress in quail - Şahin, Nurhan; Orhan, C.; Tuzcu, M.; Juturu, V.; Şahin, Kazım (Taylor & Francis Ltd, 2017)
1. To examine the molecular mechanism of capsaicinoid supplementation from capsicum extract, laying Japanese quail (n=180, 5weeks old) were reared either at 22 degrees C for 24h/d (thermoneutral, TN) or at 34 degrees C for 8h/d (heat stress, HS) and fed on one of three diets containing 0, 25 or 50mg of capsaicinoids per kilogram for 12weeks (2x3 factorial arrangement). 2. The results revealed that exposure to HS decreased feed consumption by 10.7% and egg production by 13.6%, increased serum and ovary malondialdehyde (MDA) levels by 66.9% and 88.1%, respectively, and reduced ovary superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) activities by 28.3%, 48.7% and 43.8%, respectively. 3. There were magnifications in the ovary nuclear factor kappa-light-chain-enhancer of activated B cell (NF-kappa B) levels by 42.4% and suppressions in nuclear factor (erythroid-derived 2)-like 2 (Nrf2), protein kinase B (Akt) and haem-oxygenase 1 (HO-1) levels by 29.2%, 38.2% and 30.7%, respectively, in heat-stressed quail. 4. With increasing supplemental capsaicinoids, there were linear increases in egg production, antioxidant enzyme activity, linear decreases in ovary MDA and NF-B levels and linear increases in ovary Nrf2, Akt and HO-1 levels at a greater extent in quail reared under TN condition than those reared under HS condition. Two-way treatment interactions showed that the degree of restorations in all response variables was more notable under the HS environment than under the TN environment as supplemental capsaicinoid level was increased. 5. In conclusion, capsaicinoid supplementation alleviates oxidative stress through regulating the ovary nuclear transcription factors in heat-stressed quail.
Keywords: Antioxidant status; capsaicinoids; NF-kappa B; Nrf2